Antispermatogenic Activity of the Benzothiazoline Ligand and Corresponding Organoantimony(V) Derivative in Male Albino Rats (Bioinorganic Chemistry and Applications)
Triphenylantimony(V) derivative, Ph 3 Sb( OPr i )[ SC 6 H 4 N:C( CH 3 ) CH 2 C( O ) CH 3 ] , 1b , and the corresponding benzothiazoline ligand [1, 2], H NC 6 H 4 SC ︹ ( CH 3 ) CH 2 C( O ) CH 3 , 1a , have been tested for their effects on the reproductive system of male albino rats. The oral administration of both 1a and 1b at the dose level of 10 mg/rat/day produced significant reduction in the weights of testes, epididymides, seminal vesicles, and ventral prostate. Significant decrease in sperm motility as well as in sperm density resulted in 100% sterility. Significant ( P<.01 ) alterations were also found in biochemical parameters of reproductive organs in treated male rats as compared to the control group. Production of preleptotene, pachytene, and secondary spermatocytes was decreased by 42%, 43%, 39%, and by 44%, 49%, 55% in the ligand, 1a , and organoantimony(V) derivative, 1b , treated rats, respectively. These results indicate that both compounds 1a and 1b are antispermatogenic in nature and on oral administration in male rats, and finally caused sterility. A comparison indicates that the organoantimony(V) derivative 1b is more effective pertaining to its antispermatogenic activity than the corresponding ligand 1a .